Penerapan Model Pembelajaran Problem Based Learning Dalam Mengembangkan Kemampuan Kognitif Dari Hasil Belajar Musik Barat Pada Peserta Didik Kelas XI MIPA 1 SMAN 3 Denpasar - I Ketut Muada; Muhammad Irfan Syahputra (International Forum of Researchers and Lecturers, 2024)
Viewed through the lens of arts and culture course results, students' cognitive capacities This is because classrooms are still using ineffective methods of instruction that discourage students from working on their skills in a variety of settings. The purpose of this study is to use the problem-based learning (PBL) approach to education in the arts and cultural topics (music arts) with the objective of enhancing students' cognitive capacities. The four phases of classroom action research (1) planning, (2) implementing, (3) observing, and (4) reflecting make up the study methodology. Observation and multiple-choice tests are two methods used to gather data. Qualitative and quantitative descriptive methods are used in data analysis. There was an increase from 34 students in the first cycle who finished the KKM to 36 students in the second cycle, indicating that students' cognitive abilities improved. It follows that students' cognitive capacities may be enhanced by the problem based learning (PBL) model's implementation